Suicide Intervention in Schools: If Not School Counselors, Then Who? - Laura Gallo; Carrie A. Wachter Morris (Teaching and Supervision in Counseling, 2022)
Youth suicide rates continue to rise each year. School counselors play an essential role in preventing suicide within K-12 schools. After the publication of the article, “Suicide Assessments: The Medical Profession Affirms School Counselors’ Truth,” in 2021 by Dr. Carolyn Stone, some confusion surfaced regarding professional school counselors’ responsibilities and liabilities around issues of suicide. To provide clarification, the role and training of school counselors are highlighted to provide evidence for their place in suicide risk assessment. Ethical implications and previous legal cases are provided to inform the profession. Training/supervision recommendations for counselor educators are also discussed.
Keywords: suicide assessment; school counseling; suicide intervention; suicide risk assessment